Virtual learning environments concepts, methodologies, tools and applicationsInformation (IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2012)
"This reference is a three volume compendium of the latest research, case studies, theories, and methodologies within the field of virtual learning environments, covering a wide range of subjects, spanning from authors across the globe and with applications at different levels of education and higher learning"--Provided by publisher.